Childfree and happy: transforming the rhetoric of women's reproductive choices - Wooten, Courtney Adams, author; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
Childfree and Happy examines how millennia of reproductive beliefs have positioned women who choose not to have children as deviant. Considering affect and emotion alongside the lived experiences of women who have chosen not to have children, Wooten offers a new lens to feminist scholars' examinations of reproductive rhetorics.--Provided by publisher.
Normalizing childfreedom: affect, reproductive doxa, and childfree rhetorics -- Hegemonic mothering ideologies and gendered happiness scripts -- Reproductive commonplaces and rhetorical roadblocks -- Reproductive arguments and identity work -- The limits of re-articulating hegemonic reproductive beliefs -- New articulations of childfree women's identities -- Conclusion: No regrets? Happiness and reproductive doxa.
Keywords: Childfree choice -- Social aspects; Childlessness -- Social aspects; Happiness -- Social aspects; Women -- Identity -- Social aspects; Feminism and rhetoric